Ocena wartości rokowniczej osoczowego stężenia białka C-reaktywnego oznaczonego metodą o wysokiej czułości (hs-CRP) u chorych z przewlekłą niewydolnością serca = Usefulness of serum high-sensitivity C-reactive protein (hs-CRP) level as prognostic factor in patients with chronic heart failure - Rogowicz, Daniel; Wołowiec, Łukasz; Banach, Joanna; Buszko, Katarzyna; Mosiądz, Przemysław; Gilewski, Wojciech; Zukow, Walery; Sinkiewicz, Władysław (Journal of Education, Health and Sport, 2016)
Rogowicz Daniel, Wołowiec Łukasz, Banach Joanna, Buszko Katarzyna, Mosiądz Przemysław, Gilewski Wojciech, Zukow Walery, Sinkiewicz Władysław. Ocena wartości rokowniczej osoczowego stężenia białka C-reaktywnego oznaczonego metodą o wysokiej czułości (hs-CRP) u chorych z przewlekłą niewydolnością serca = Usefulness of serum high-sensitivity C-reactive protein (hs-CRP) level as prognostic factor in patients with chronic heart failure. Journal of Education, Health and Sport. 2016;6(7):513-524. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.58867 http://ojs.ukw.edu.pl/index.php/johs/article/view/3715 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2016. Revised 15.07.2016. Accepted: 26.07.2016. Ocena wartości rokowniczej osoczowego stężenia białka C-reaktywnego oznaczonego metodą o wysokiej czułości (hs-CRP) u chorych z przewlekłą niewydolnością serca Usefulness of serum high-sensitivity C-reactive protein (hs-CRP) level as prognostic factor in patients with chronic heart failure Daniel Rogowicz1, Łukasz Wołowiec1, Joanna Banach1, Katarzyna Buszko2, Przemysław Mosiądz3, Wojciech Gilewski1, Walery Zukow4, Władysław Sinkiewicz1 1II Katedra Kardiologii, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 2Katedra Podstaw Teoretycznych Nauk Biomedycznych i Informatyki Medycznej, Wydział Farmaceutyczny, Uniwersytet Mikołaja Kopernika w Toruniu 3Studenckie Koło Naukowe Diagnostyki i Terapii Niewydolności Serca, II Katedra Kardiologii, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 4Instytut Kultury Fizycznej, Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie Wstęp: Niewydolność serca (NS) jest schorzeniem kardiologicznym, które charakteryzuje się stale rosnącą zapadalnością i znaczną śmiertelnością. Wciąż trwają poszukiwania markerów biochemicznych, które pomogłyby lepiej opisać tę grupę pacjentów i posłużyły jako czynniki rokownicze w przewidywaniu zgonu u chorych z NS. Cel: Celem pracy była ocena wartości rokowniczej osoczowego stężenia białka C-reaktywnego oznaczonego metodą o wysokiej czułości (hs-CRP) u chorych z przewlekłą niewydolnością serca, jako ewentualnego predyktora zgonu w ciągu 24–miesięcznej obserwacji chorych ze skurczową przewlekłą niewydolnością serca (PNS). Materiał i metody: Badaną grupę stanowiło 165 pacjentów hospitalizowanych z PNS w II – IV klasie wg NYHA. U wszystkich pacjentów z grupy badanej przy przyjęciu wykonano rutynowe badania laboratoryjne, a także oznaczono osoczowe stężenie białka C-reaktywnego metodą turbidymetryczną o wysokiej czułości (hs-CRP), osoczowe stężenie ferrytyny oraz osoczowe stężenie N-końcowego propeptydu natriuretycznego typu B (NT-proBNP). Grupę kontrolną stanowiło 31 zdrowych ochotników. Jako punkt końcowy badania ustalono zgon z dowolnej przyczyny, a okres obserwacji wynosił 24 miesiące. Wyniki: W trakcie dwuletniego okresu obserwacji zmarło 28,5% pacjentów. Charakteryzowali się oni istotnie wyższą klasą NYHA, niższą frakcją wyrzutową oraz wyższymi medianami osoczowych stężeń hs-CRP, troponiny T i NT-proBNP. Porównując grupę badaną z grupą kontrolną wykazano, że osoczowy poziom hs-CRP różnił się istotnie statystycznie pomiędzy obiema grupami. W analizie jednoczynnikowej przeprowadzonej według modelu hazardu proporcjonalnego Cox’a wykazano istotny statystycznie wpływ na wystąpienie punktu końcowego następujących parametrów: klasy NYHA (p = 0,007), EF (p = 0,018), hs-CRP (p = 0,002), NT-proBNP (p < 0,001) oraz BMI (p = 0,0496). W analizie wieloczynnikowej wykazano, że hs-CRP (p = 0,028, HR=1,032), NT-proBNP(p = 0,007; HR = 1), klasa NYHA (p = 0,032; HR = 0,453) oraz BMI (p = 0,048, HR=1,051) są niezależnymi, istotnymi statystycznie czynnikami wpływającymi na wystąpienie zgonu w obserwowanej grupie chorych. Proponowany punkt odcięcia dla hs-CRP wyliczony na podstawie krzywej ROC wyniósł 11,99 mg/L, AUC=0,617 (0,521-0,712), p=0,0168, natomiast dla NT-proBNP wyniósł 1615 pg/ml, AUC=0,659 (0,569-0,75), p= 0,0005. Nie zaobserwowano istotnej statystycznie różnicy w mocy diagnostycznej testów pomiędzy hs-CRP i NT-proBNP. Dla poszczególnych punktów odcięcia dokonano analizy przeżycia Kaplana-Meiera i wykazano, że proponowane punkty odcięcia zarówno dla hs-CRP (p < 0,001), jak i NT-proBNP (p = 0,006) dzielą chorych na dwie grupy z istotnie statystycznie różnicą w długości życia. Podwyższone stężenia hs-CRP i NT-proBNP wiązały się z dużo większym ryzykiem wystąpienia zgonu, niż w przypadku tylko podwyższonego stężenia NT-proBNP. Wnioski: Osoczowe stężenie hs-CRP można uważać za wartościowy marker rokowniczy zgonu u chorych hospitalizowanych z rozpoznaniem skurczowej przewlekłej niewydolności serca w II-IV klasie wg NYHA. Słowa kluczowe: przewlekła niewydolność serca, hs-CRP, rokowanie. Abstract Introduction: Heart failure (NS) is a cardiological disease which is characterised by a constantly increasing morbidity and mortality rates. There are still searches for bio-chemical markers which better describe this group of patients and which may be used as prognostic factors in forecasting repeated hospitalization and death for patients with NS. Aim: The goal of this paper was to assess the usefulness of marking the highly specific C-reactive protein (hs-CRP) as a potential predicator for death within a 24-month follow-up in patients with systolic chronic heart failure (PNS). Methods: The study group was comprised of 165 patients with chronic NYHA II-IV class heart failure who were hospitalized. All patients from the examined group underwent, on admission, routine lab tests as well as they were tested for the plasmatic concentration of protein C-reactive with a turbidimetric method with high sensitivity (hs-CRP), plasmatic concentration of ferritin and plasmatic concentration of N-final pro-peptide natriuretic type B (NT-proBNP). 31 healthy individuals served as negative controls. The follow-up period took 24 months and the endpoint included the death for any reason during the follow-up. Results: 28.5% of patients died during a 2-year follow-up. Those patients were characterized by significantly statistically higher NYHA class, lower ejection fraction and higher plasma concentration medians of hs-CRP, troponin T and NT-proBNP. The comparison of the examined group and the control group has shown that the plasmatic hs-CRP level was statistically different in both groups. In univariate analysis, a statistically significant impact on the occurrence of the endpoint was observed: NYHA class (p = 0,007), EF (p = 0,018), hs-CRP (p = 0,002), NT-proBNP (p < 0,001) oraz BMI (p = 0,0496). Multivariate analysis has shown that hs-CRP (p = 0,028), NT-proBNP (p = 0,007), NYHA class (p = 0,032) and BMI (p = 0,048) are independent significant predictors of death. In the ROC analysis the suggested cut-off point for hs-CRP amounted to 11,99 mg/L, AUC=0,617 (0,521-0,712), p=0,0168, whereas for NT-proBNP it was 1615 pg/ml, AUC=0,659 (0,569-0,75), p=0,0005. No statistically significant difference in the power of diagnostic tests was observed between of hs-CRP and NT-proBNP. For particular cut-off points, Kaplan- Meier survival analysis was conducted. It was demonstrated that the suggested cut-off points for both hs-CRP (p<0.001) and NT-proBNP (p=0.006) divide patients into two groups showing statistically significant differences in terms of overall survival. Increased concentrations of hs-CRP and NT-proBNP were connected with higher risk of death than an increased concentration of NT-proBNP itself. Concentration: It seems that plasmatic concentration of hs-CRP can be considered as a valuable predictor of death in patients hospitalized with systolic chronic heart failure in NYHA class II-IV. Key words: chronic heart failure, hs-CRP, prognosis.